Sports on television - Marill, Alvin H. (Praeger television collection., 2009)
Television has always augmented its dramatic and variety programming with sports. After covering wrestling and boxing matches for several years, ABC added the hugely popular Roller Derby between 1949 and 1951, and later, college and pro football. Today, there is a multitude of pay and cable networks devoted exclusively to baseball, football, golf, hockey, tennis, ice-skating, and auto racing. Rather than focusing on live sports broadcasts, however, this book chronicles the history of sports-themed comedies and dramas, to see how our national fictions have affected our authentic sports experiences, and vice versa. Sports dominate the television landscape today, and still the demand for more is so great that pay and cable networks continue to find funding and success, even when devoted exclusively to a single sport. But this is really nothing new: television has always augmented its dramatic and variety programming with sports. Live sports have had a tremendous impact on what we see on television, and on how we see it. Rather than focusing on live sports broadcasts, however, this book takes a critical look at sports-themed comedies and dramas, to see how our authentic sports affect our national fictions as well. From the character studies that supplement Olympic coverage, to nightly highlight reels, to reality programming on ESPN, sports both echo and help shape the myths that pervade our culture. Sports on Television covers the changing relationship between live sports broadcasts and television dramas, as well as the important technological developments and cultural shifts that have changed the way we view the reality of sports. In 1949, after covering wrestling and boxing matches for several years, ABC added the hugely popular Roller Derby, and later moved on to college and pro football, where humble beginnings have since developed into a national obsession. In the early sixties Jimmy Stewart played a disgraced baseball player in Flashing Spikes-which was also one of the rare ventures into television for veteran director John Ford. On HBO the Yankees have been the subject of both 61* - about Roger Maris's quest to top Babe Ruth's home run record - and The Bronx Is Burning, about the 1977 Yankees team. And there have been sports-themed TV sitcoms as well, such as Sports Night, Aaron Sorkin's critically lauded but commercially unsuccessful project, which preceded his work on The West Wing. Meanwhile American Gladiators-a strange blend of canned programming and authentic athletic endeavor that in effect puts television audiences in an arena with what amounts to professional athletes-is quickly becoming one of the most popular shows on primetime. Here, Marill gives due time to all of these unique projects.